Knowledge of the general physicians on surgical ethics especially on informed consent among surgically emergency patients in Chittagong Medical College Hospital, Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3868Journal of Chittagong Medical College Teachers' Association 2008: 19(2):33-38